Minimising stresses in double wall transpiration cooled components for high temperature applications. (1st January 2021) - Skamniotis, Christos; Cocks, Alan C.F.
Abstract: To allow further increase in gas turbine efficiency, engine core temperatures need to exceed the natural capabilities of metals, necessitating state-of-the-art cooling technologies, such as double-wall transpiration cooling systems. Despite these systems offer excellent cooling effectiveness, they come at the cost of thermal stresses which continue to raise longstanding thermomechanical performance concerns that have hindered their implementation. We present a two-dimensional (2D) analytical-Finite Element (FE) analysis of double-wall transpiration cooled configurations, which characterises a variety of thermoelastic stress scenarios and provides the means for systematically minimising critical thermal stresses through clever design strategies. We find that peak stresses are modified with geometric features differently for different underlying structural constraints. For double walls with free-unconstrained ends, the general geometric periodicity of the system implies that the wall rotations are equal and non-zero, such that minimising the spacing between the two walls and the cooler/inner wall thickness both improve mechanical performance. For self-connected walls and cylindrical-like geometries, the rotations are constrained, while the walls must extend equally; increasing the density of connecting pedestals here as well as the cooler/inner wall thickness both minimise the critical tensile stresses at the pedestal-wall fillets, but degrade creep-fatigue performance at the external hot surface of the system. The advantage of our simplified, 2D analysis is that it provides analytical relationships for the effect of a range of geometric parameters on structural performance, which are essential for interpreting larger scale simulation data. Relationships of this type are valuable for use in conceptual and preliminary design and provide the foundation for creep-fatigue life evaluations in a range of double wall transpiration cooling configurations.